Can Limits to Arbitrage Explain Stock Price Idiosyncratic Volatility Premium Puzzle in China’s A-Share Market? - Xiaohui Chen; Jianhua Ye (Discrete Dynamics in Nature and Society, 2021)
Investigating the existence and causes of idiosyncratic volatility premium puzzle in developing stock market can enrich the research on this asset pricing puzzle. To investigate the existence and whether limits to arbitrage in China’s A-share market can explain the idiosyncratic volatility premium puzzle, this paper uses listed stocks in China’s A-share market from 2002 to 2019 as a sample. We calculate three individual measures and one comprehensive measure of limits to arbitrage based on Chinese specific regulations. After that, we conduct univariate portfolios analysis, regression analysis, and bivariate portfolios analysis to obtain evidence. We prove that idiosyncratic volatility premium puzzle exists in China’s A-share market and is robust and that limits to arbitrage in this market can partly explain this asset pricing puzzle. This paper enriches research on asset pricing anomaly and can help us evaluate the effect of China’s A-share market reform.